2015
DOI: 10.1016/j.chaos.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness as a state of matter

Abstract: We examine the hypothesis that consciousness can be understood as a state of matter, "perceptronium", with distinctive information processing abilities. We explore four basic principles that may distinguish conscious matter from other physical systems such as solids, liquids and gases: the information, integration, independence and dynamics principles. If such principles can identify conscious entities, then they can help solve the quantum factorization problem: why do conscious observers like us perceive the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
134
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 42 publications
4
134
0
3
Order By: Relevance
“…The study of molecular mechanisms is not necessarily in competition with such theories. However, one assumption often made in this context is the assumption of "substrate-independence" (compare this also to the "robustness assumption" in [10]) which is incompatible with the assumption that changes in molecular organization are relevant to changes in phenomenology. After all, assuming substrate-independence guarantees that we could neglect any influence that "lower lying" levels might have on the phenomenon under study.…”
Section: Information-processing Theories Of Consciousnessmentioning
confidence: 95%
“…The study of molecular mechanisms is not necessarily in competition with such theories. However, one assumption often made in this context is the assumption of "substrate-independence" (compare this also to the "robustness assumption" in [10]) which is incompatible with the assumption that changes in molecular organization are relevant to changes in phenomenology. After all, assuming substrate-independence guarantees that we could neglect any influence that "lower lying" levels might have on the phenomenon under study.…”
Section: Information-processing Theories Of Consciousnessmentioning
confidence: 95%
“…Представляется вполне ес-тественной попытка создания формальной теории для математического описания взаимодей-ствия ментальных объектов -идей, ассоциаций, мыслей -в пространстве бессознатель-ного [10]. Для этого необходимо выбрать соответствующую систему координат и установить законы перехода системы из одного состояния в другое.…”
unclassified
“…The main open question of this approach seems to be what defines the "frog perspective" or -in Tegmark's words -the "factorization" [15] into subject, object and environment. Obviously this perspective is a consequence of the observer's consciousness being confined to her cerebral cortex.…”
mentioning
confidence: 99%
“…• More recently Tegmark applied IIT to quantum systems and found that due to the free choice of the Hilbert space basis only an insufficient maximum integrated information of 0.25 bits can be obtained [15].…”
mentioning
confidence: 99%